2011
DOI: 10.1186/1471-2334-11-24
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of healthcare workers in Chinese intensive care units regarding 2009 H1N1 influenza pandemic

Abstract: Background: To describe the knowledge and attitudes of critical care clinicians during the 2009 H1N1 influenza pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 26 publications
6
49
1
Order By: Relevance
“…Some PHEs are common, such as severe weather events. 6,10,[19][20][21][22][23][24][25][26][27] However, for a mass-casualty incident, 83%-90% of study participants implied they were willing to respond to such events as an airplane crash or tornado. The nature of a PHE appears to influence HCP's responses.…”
Section: Nature Of the Phementioning
confidence: 99%
“…Some PHEs are common, such as severe weather events. 6,10,[19][20][21][22][23][24][25][26][27] However, for a mass-casualty incident, 83%-90% of study participants implied they were willing to respond to such events as an airplane crash or tornado. The nature of a PHE appears to influence HCP's responses.…”
Section: Nature Of the Phementioning
confidence: 99%
“…For the planning of effective risk communication, it is necessary to assess the public's knowledge level to determine vulnerable target groups. Multiple cross-sectional studies have been done to assess knowledge and attitude of the public on past respiratory disease outbreaks [13][14][15][16][17][18]. Ethnicity, age and education level were found to influence an individual's knowledge level of infectious outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…A simulation study by Swaminathan and the colleagues reported that, for a patient with suspected avian or pandemic influenza who was not clinically unwell or hypoxic, the mean number of close contacts was 12.3 (range 6-17; 85% HCWs), and mean exposures were 19.3 (range [15][16][17][18][19][20][21][22][23][24][25][26] during the first 6 hours in the emergency departments [7]. In comparison, critical care clinicians are likely to encounter even more repeated close contacts, and are at significantly high risk of acquiring such an infectious disease during patient care.…”
Section: Introductionmentioning
confidence: 99%